Analysis of the Relevant Factors for the Engaging Women in Various Sports in Croatia - Joško Sindik; Zlatka Kozjak Mikić; Lucija Dodigović; Sanda Čorak (Montenegrin Sports Academy, 2016)
Goals of this research were to determine the correlations among the dimensions of relevant factors about engagement of women in sports, as well as to determine the differences in the dimensions of relevant factors about engagement of women in sports, according to several independent variables: type of sport, educational level, marital status and place of living. A total of 342 female athletes and other sport practitioners are examined, with the average age of 31.53±13.92 years (M±SD) from several Croatian sport federations: judo, badminton, gymnastics, bowling, acrobatic rock'n roll, handball, sport fishing, Association of the deaf athletes, archery, chess and basketball. The results revealed that according to the type of sport, the differences are statistically significant for: negative environment, relaxation/fun and ambition/self-esteem motives; environmental, obligation and financial/traffic/rules barriers; indirect strategies and already present initiatives for including women in sports. According to the education level, the differences are statistically significant for: positive personal, negative environmental motives and ambition/self-esteem motives; obligations as the barriers; organization out-of-sport commitments and specific strategies for media. The differences in the marital status of participants are statistically significant for the variables: positive personal, negative environmental and ambition/self-esteem motives; environmental and obligation barriers; organization of out-of-sport commitments. At last, only two statistically significant differences are found according to the place of living: for indirect strategies for including women in sports and for the programs created only for women. The results provide the platform for developing programs and strategies for retaining and engaging women in particular sports in Croatia.